Attitude and Practices of Community, Government and Corporate Sector Pharmacists towards Pharmaceutical Care in Maharashtra - Pawar, Sunita; Pawar, Atmaram (Journal of Pharmacy Practice and Community Medicine)
Background: Pharmacist can directly influence disease management by providing community based Pharmaceutical Care services. Pharmacists must evolve from dispensers to medication management practitioners. Therefore their knowledge, attitude and practices are the key necessities, so that they can work along with physicians to significantly improve the health of the patients. Objective: To assess the Attitude and Practices of Pharmacists regarding Pharmaceutical Care. Methods: This prospective study administered validated Attitude and Practices questionnaire on a sample of 508 pharmacists belonging to government, community and corporate sectors of Pune district in India. The level of attitude and practices towards pharmaceutical care were assessed with simple descriptive analysis and the outcomes from focused group discussion with higher officials from all three sectors. Results: The responses of all participants were significantly low across all components of Pharmaceutical care practices including patient counseling, solving drug related problems, doing interventions, ADR management and informing drug interactions, whereas the attitude to provide these services was found to be very high. From Focused group discussion with officials, it was confirmed that Pharmacists did not practice much patient care services due to barriers like lack of proper education and training of pharmacists, weak implementation of existing laws, inadequate clinical knowledge and lack of recognition of the pharmacy profession by other healthcare professionals. Conclusion: The study concluded that in India, dispensing of medicines still remains as a dominant service provide by all pharmacists and there is very limited practice of Pharmaceutical Care in spite of positive attitude of pharmacists towards it.
Keywords: Pharmacists; Attitude and practice; Pharmaceutical care; India